Conservation of Circellium bacchus Fabricius (Coleoptera: Scarabaeidae) : genetic population structure and ecological preferences - Scholtz, Clarke H. (University of Pretoria, 2022)
Dissertation (MSc (Entomology))--University of Pretoria, 1998.